Aging Population and Canadian Public Pension Plans - Bayoumi, Tamim (IMF Working Papers; Working Paper, 1994)
Canadian public pension plans are run on a "pay-as-you-go" basis. As the baby boom ages, contribution rates for the two main plans are projected to rise significantly, from their current level of around 5 percent of eligible earnings to over 13 percent by 2030. An alternative is to set contribution rates at their underlying long-term levels. Such a policy would imply a significant rise in current contribution rates, to 10-10 1\2 percent of eligible earnings, but would allow the system to cope with the retirement of the baby boom generation without recourse to borrowing or significant increases in contribution rates.